ANALYSIS OF FINANCIAL RATIOS TO ASSESS FINANCIAL PERFORMANCE AT PT. UNILEVER INDONESIA TBK - Tri Damayanti; Nur Halimah (International Journal Multidisciplinary Science, 2023)
This study aims to analyze the financial performance of PT. Unilever Indonesia Tbk during the 2012-2021 period seen from the Liquidity Ratio, Solvency Ratio, and Profitability Ratio. The data analysis technique used is financial ratios, namely liquidity ratios, solvency ratios, and profitability ratios. The results of the study show that: Liquidity ratios with measuring instruments using current ratios, very current ratios and cash ratios show "less good" results when compared to the industry average. The solvency ratio with a measurement tool for calculating using the ratio of debt to assets and the ratio of debt to capital which shows "unfavorable" results when compared to the industry average. Profitability ratios with measuring tools calculations using the ratio of return on assets and the ratio of return on equity shows "good" results.